Synthesis of lipids and N-containing molecules 2 - Feigenson, Gerald W. (Henry Stewart Talks, 2020)
Summary of ‘activated’ molecules, Cholesterol biosynthesis, Lipoproteins and their roles, Synthesis of N-containing molecules, Control of all metabolism
Reviewed at 2022/11/27